Impact of Tax Reduction Policy on Banking Sector in Pakistan - Lodhi, Khalid Mahmood (Information Management and Business Review, 2011)
This study analyzes the impact of tax policy reforms on the profits of banking sector. The empirical results of unit root and Augmented Dickey Fuller (ADF) test reveal that the data series of tax is positively skewed whereas data series of profitability is negatively skewed. The kurtosis value indicates that all the series are platykurtic. From the value of ADF statistics, it is evident that all the variables are non-stationery at log level and are stationary at their first difference. Granger Causality Test shows that profitability of banking does not granger because tax but tax granger cause profitability of banking which depicts that the change in tax rate affects the profitability of banking industries. The study finds that reduction in corporate income tax rates for banking sector has produced positive impact in shape of increased banking sector profits and assets during the period under review.